ROW SPACING EFFECT ON SOIL AND LEAF WATER STATUS OF SUMMER SOYBEAN - X. B. Zhou; L. Qi; G. M. Yang; Y. H. Chen (Journal of Animal and Plant Sciences, 2011)
The effects of row spacing (RS) on soil water content (SWC), leaf relative water content (RWC), leaf water potential (Ψ), and osmotic potential (π) were investigated in summer soybean crops in Northern China during the 2007 and 2008 growing seasons. The experiment consisted of five planting patterns resulting in the same plant population density (3.09 × 105 plant·ha-1), with RS of 18, 27, 36, 45, and 54 cm. A significant negative correlation was observed between RS and SWC, RWC, Ψ, π, Y in both years (P < 0.05). SWC, RWC, Ψ, and π correlated positively with Y in soybean. The daily rainfall caused fluctuations in SWC. In 2007 and 2008, the mean values of RWCs, Ψ, and π for RS 18 and 27 were significantly higher than that of RS 54 (P < 0.05). At the grain-filling stage, the hourly Ψ of the different RS treatments produced a V-shaped curve trend in one day, and the minimum of the curve appeared in midday. These results indicated that this was a beneficial response for yield under the high SWC, RWC, Ψ, and π conditions. Therefore, narrow RS improved soil and leaf water status and could increase yield of crops.
Keywords: Glycine max; soil water content; leaf relative water content; leaf water potential; leaf osmotic potential